Meiofauna stable isotope values (δ13C, δ15N) and individual body mass from sediment samples collected with a multicorer at six deep-sea stations in the Southern Ocean (PS71 SYSTCO 2007-2008) - Gritta Veit-Köhler; Katja Guilini; Marco Bruhn; Christoph Mayr (PANGAEA, 2024)
We provide δ13C and δ15N stable isotope data and individual body mass [μg C, μg N] for two meiofauna taxa (Nematoda and Copepoda) from sediment samples collected in bathyal and abyssal depths (1927–5338 m) along a 2400-km North-South transect in the Atlantic part of the Southern Ocean. During the RV Polarstern expedition PS71 (ANT XXIV-2 SYSTCO, 28 November 2007 until 04 February 2008) six deep-sea stations were sampled from the Polar Front in the north (49°S), over the southern Polar Front (52°S, this site was visited two times), the Central Weddell Sea (62°S), and the seamount Maud Rise (64°S) to the Lazarev Sea (70°S) in the south. Samples (cores) were collected at each station with a MUC10 multicorer. On board, sediment from the upper layer (0–5cm) of the respective core was scooped off, pre-sieved and stored at -80°C. In the laboratory, samples were prepared for stable isotope analyses, which were carried out as described by Veit-Köhler et al. (2013). Values for Nematoda of the size class 1000–300 μm are given but were not used by Veit-Köhler et al. (2013). Data were obtained for a study on Southern Ocean deep-sea meiofauna, their stable isotope composition, relation to surface productivity, and their reaction to phytoplankton blooms (see "Related to" below). An isotope ratio mass spectrometer (Delta Plus, Thermo-Finnigan) coupled to an elemental analyzer (NC 2500, Carlo Erba; combustion temperature 1080 C) at the GeoBio-Center (University of Munich, Germany) was used to measure carbon and nitrogen stable isotope ratios and elemental contents (wt% N and C) on the same sample.